2021
DOI: 10.3389/fpsyg.2021.694583
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management in Anxiety and Depression: A Psychometric Evaluation of a Questionnaire

Abstract: Objective: To examine the underlying factor structure and psychometric properties of the Assessment of Self-management in Anxiety and Depression (ASAD) questionnaire, which was specifically designed for patients with (chronic) anxiety and depressive disorders. Moreover, this study assesses whether the number of items in the ASAD can be reduced without significantly reducing its precision.Methods: The ASAD questionnaire was completed by 171 participants across two samples: one sample comprised patients with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We also found that the extent of depressiveness or rather the severity of the depressive syndrome seems to be associated with the patientś self-management competence ( hypothesis 2 ). As shown by Orem (2001), Fox (2017), Krijnen-de Bruin (2021) and in our previous work Wehmeier et al (2019), the ability of patients to make use of their self-management skills is influenced by the current severity of their depressive symptoms, with a higher symptom severity leading to a decrease in self-management skills. The present study allows a similar conclusion.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We also found that the extent of depressiveness or rather the severity of the depressive syndrome seems to be associated with the patientś self-management competence ( hypothesis 2 ). As shown by Orem (2001), Fox (2017), Krijnen-de Bruin (2021) and in our previous work Wehmeier et al (2019), the ability of patients to make use of their self-management skills is influenced by the current severity of their depressive symptoms, with a higher symptom severity leading to a decrease in self-management skills. The present study allows a similar conclusion.…”
Section: Discussionmentioning
confidence: 73%
“…All statistical analyses were performed using SAS (SAS Institute Inc., 2013) or SPSS (IBM Corp., 2017, 2021. With regard to measures of central tendencies and variation, the statistical mean (M) ± its standard deviation (SD) is reported.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Our researches show that 20% up to 65% of women are anxious, and also due to their relationships with children, they could pass it on to kids (Krijnen-de Bruin et al, 2021). Therefore, anxious mothers have a higher sense of cohesion than normal mothers, which is a useful tool for dealing with tensions and solving problems and developing social coping skills (Fossion et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Depression and anxiety are conditions that increase globally in adolescents and impair the functionality of patients. 30 The general characteristic of patients with depression, distractibility and anxiety is that they do not pay attention to self‐care and hygiene 31 ; since it is known that self‐management and drug treatment compliance are impaired, it may be difficult to keep the wound clean and hairless in these patients. 32 In the series consisting of adolescents with an average age of 15, it is stated that in this situation where wound care has to be done locally by a second person, children in the polyclinic are often disturbed by this, and they do not want to have it done.…”
Section: Discussionmentioning
confidence: 99%